2016
DOI: 10.3847/2041-8205/830/1/l3
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Resolved HCN Absorption Features in the Circumnuclear Region of NGC 1052

Abstract: We present the first VLBI detection of HCN molecular absorption in the nearby active galactic nucleus NGC 1052. Utilizing the 1 mas resolution achieved by the Korean VLBI Network, we have spatially resolved the HCN absorption against a double-sided nuclear jet structure. Two velocity features of HCN absorption are detected significantly at the radial velocity of 1656 and 1719 km s −1 , redshifted by 149 and 212 km s −1 with respect to the systemic velocity of the galaxy. The column density of the HCN molecule … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 38 publications
2
18
0
Order By: Relevance
“…The flux densities of the central component within 1.6 mas (the major axis of the synthesized beam), the eastern jet, and the western jet are determined to be 414, 92, and 93 mJy, by summing the CLEAN components. The continuum image is consistent with the previous KVN map at 89 GHz taken in 2015 (Sawada-Satoh et al 2016).…”
Section: Observations and Data Reductionsupporting
confidence: 90%
See 1 more Smart Citation
“…The flux densities of the central component within 1.6 mas (the major axis of the synthesized beam), the eastern jet, and the western jet are determined to be 414, 92, and 93 mJy, by summing the CLEAN components. The continuum image is consistent with the previous KVN map at 89 GHz taken in 2015 (Sawada-Satoh et al 2016).…”
Section: Observations and Data Reductionsupporting
confidence: 90%
“…During a time gap of 27 months between the two observations of HCN and HCO + , the background receding jet component could move 0.18 pc outward, almost one beam size. Adopting an abundance ratio HCO + relative to H 2 of (2-3) ×10 −9 in Galactic diffuse molecular gas (Liszt & Lucas 2000Liszt et al 2010), the column density of molecular hydrogen (H 2 ) is derived to be N H 2 ∼ 10 24 -10 25 cm −2 , which is consistent with N H 2 estimated from the HCN absorption spectrum (Sawada-Satoh et al 2016).…”
Section: Discussionsupporting
confidence: 71%
“…For 3C 84, non-detection of receding jet at low frequencies cannot be explained entirely by the Doppler debeaming effect, and therefore, free-free absorption due to the ionized gas is inferred (Walker et al 2000). For NGC 1052, Kameno et al (2001) found the presence of a torus-like ionized absorber around the nucleus in addition to molecular gas at outer radii with very high column densities (Sawada-Satoh et al 2016. It has been argued that these distributions suggest a transition from spherical radial accretion flow to rotational accretion orbits (see also, Kameno et al 2003Kameno et al , 2005Sawada-Satoh et al 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Very high opacity (τ 1000) has been observed within about 2 mas ( 0.2 pc) from the estimated position of the SMBH, obscuring the receding jet (Sawada-Satoh et al 2008). Multiple molecular species have been observed as masers or absorbers at comparable angular scale (Claussen et al 1998;Vermeulen et al 2003;Impellizzeri et al 2008), leading to estimates of N H in the CT regime in at least some parts of the obscuring torus (Sawada-Satoh et al 2016, 2019.…”
Section: Introductionmentioning
confidence: 97%